國小實施教師專業發展評鑑影響因素量表發展之研究: 以影響組織變革環境因素、組織變革策略、教師個人特性為主 A Study on the Development of Influencing Factor Assessment Scale of Teacher Evaluation for Professional Development in Elementary Schools: Focusing on Environment Factors Influencing Organizational Change, Organizational Change Strategies and Teacher Personal Factors - 張媛甯 Yuan-Ning Chang; 郭重明 Chung-Ming Kuo; 蘇建洲 Chien-Chou Su (National Changhua University of Education, 2016)
本研究旨在發展國小實施教師專業發展評鑑影響因素之評估量表，透過文獻探討瞭解國內外有關教師評鑑與其影響因素的理論與實務，以建立構念和發展題項。藉由焦點團體與項目分析進行題項的修正、篩選與確認，再運用探索性因素分析以純化測量工具；其次，採驗證性因素分析進行競爭模式的比較以選擇最簡效模式，繼而進行該模式的信效度檢定及測量恆等性驗證。研究結果發現，本量表整體模式適配度評估皆符合統計考驗，並具有二階層模式的因素結構，分為影響組織變革環境因素、組織變革策略及教師個人特性三個分量表，總計69 個測量題項。最後，依據研究結果，提供國 民小學與後續研究之具體建議。 The main purpose of this study was to develop an assessment scale on influencing factor of Teacher Evaluation for Professional Development (TEPD) in elementary schools. According to the literature reviews of influencing factors for implementing teacher professional development evaluation, the construct and measuring items were developed. First, the factor structure and items of the preliminary scale were confirmed by focus group experts' modifications and item analysis, and then exploratory factor analysis was conducted to purify the dimensions and measuring items of influencing factor for TEPD. Second, confirmatory factor analysis was employed to choose the best model by comparisons of model fits, and further its reliability and validity were tested. Results showed that the two-hierarchical factor structure of the scale was verified, and its goodness-of-fitness conformed to standard. The 69 items were divided into three subscales which included environment factors influencing organizational change, organizational change strategies, and teacher personal factors. Last, suggestions were offered for elementary schools and future research studies.